The Role of Information Technology in Improving Entrepreneurship Performance through Socio-Cultural Adaptation - Arief Darmawan; Lena Ellitan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study examines current literature on the impact of information technology on entrepreneurial performance through socio-cultural adaptation. This review reveals the role of information technology as a key driver of innovation and entrepreneurial growth by facilitating global communication and rapid exchange of information. However, research in the field of digital entrepreneurship still faces the challenges of fragmentation and a lack of a unified framework. An interdisciplinary approach is needed to understand the unique characteristics of adaptive and generative digital technologies. In conclusion, information technology plays a strategic role in increasing efficiency, innovation and entrepreneurial collaboration. Future research is expected to integrate various disciplines to gain a comprehensive understanding of digital entrepreneurship and develop business models that are more responsive to technological and market changes.